Human Inner Ear Immune Activity: A Super-Resolution Immunohistochemistry Study - Liu, Wei; Kämpfe Nordström, Charlotta; Danckwardt-Lillieström, Niklas; Rask-Andersen, Helge (Frontiers in Neurology, 2019)
Background: Like the brain, the human inner ear was long thought to be devoid of immune activity. Only the endolymphatic sac (ES) was known to be endowed with white blood cells that could process antigens and serve as an immunologic defense organ for the entire inner ear. Unexpectedly, the cochlear and vestibular organs, including the eighth cranial nerve, were recently shown to contain macrophages whose functions and implication in ear disease are somewhat undefined. Here, we review recent inner ear findings in man and extend the analyses to the vestibular nerve using super-resolution structured illumination microscopy (SR-SIM). Materials and Methods: Human ESs and cochleae were collected during surgery to treat patients with vestibular schwannoma and life-threatening petro-clival meningioma compressing the brainstem. The ESs and cochleae were placed in fixative, decalcified, and rapidly frozen and cryostat sectioned. Antibodies against ionized calcium-binding adaptor molecule 1-expressing cells (IBA1 cells), laminin β2 and type IV collagen TUJ1, cytokine fractalkine (CX3CL1), toll-like receptor 4 (TLR4), CD68, CD11b, CD4, CD8, the major histocompatibility complex type II (MHCII), and the microglial marker TEME119 were used. Results: IBA1-positive cells were present in the ESs, the cochlea, central and peripheral axons of the cochlear nerve, and the vestibular nerve trunk. IBA1 cells were found in the cochlear lateral wall, spiral limbus, and spiral ganglion. Notable variants of IBA1 cells adhered to neurons with “synapse-like” specializations and cytoplasmic projections. Slender IBA1 cells occasionally protracted into the basal lamina of the Schwann cells and had intimate contact with surrounding axons. Discussion: The human eighth nerve may be under the control of a well-developed macrophage cell system. A small number of CD4+ and CD8+ cells were found in the ES and occasionally in the cochlea, mostly located in the peripheral region of Rosenthal's canal. A neuro-immunologic axis may exist in the human inner ear that could play a role in the protection of the auditory nerve. The implication of the macrophage system during disease, surgical interventions, and cell-based transplantation should be further explored.